Molecular subtyping of clinical isolates vibrio cholerae from Malaysia and Vietnam by pulsed-field gel electrophoresis - Thong, Kwai Lin; Goh, Yee Ling; Phung, Dac Cam (Malaysian Society for Molecular Biology and Biotechnology, 2002)
Pulsed-field gel electrophoresis (PFGE) was applied to analyse sporadic and outbreak cases of cholera caused by V. cholerae O1 biotype El Tor from Vietnam (n=16) and V. cholerae O139 from Malaysia (n=12) and from five vaccine strains. NotI-Digestion of chromosomal DNA from these isolates, followed by PFGE produced eleven different profiles among the 16 V. cholerae O1 isolates (Dice coefficient: 0.67-0.97). The V. cholerae O1 Ogawa and Inaba strains were clearly differentiated into distinct clusters. NotI-PFGE analysis among V. cholerae O139 isolates showed a predominant PFGE profile (N12) indicating that the outbreak was probably derived a single clone. Among the five vaccine strains, the PFGE profiles of V. cholerae Inaba Cairo 48 and classical Inaba Cairo 48 were similar to some of the field isolates of 01 Inaba strains in Vietnam. The PFGE analysis showed that the V. cholerae O139 isolates from Malaysia were indistinguishable as these strains were probably derived from a cholera outbreak and the V. cholerae O1 isolates from Vietnam exhibited limited genetic diversity.